The Effect of Fiscal Independence, Private Investment, Zakat and Economic Growth on Islamic Human Development Index (IHDI) In Jambi Province Indonesia - Fathiyah Fathiyah; Amri Amir; Siti Hodijah; Zamzami Zamzami; Erni Achmad (Integrated Journal of Business and Economics (IJBE), 2026)
Human development can be measured using the Islamic Human Development Index (IHDI) indicator for countries with a majority Muslim population. Variables that affect IHDI include fiscal independence, private investment, zakat performance and economic growth. However, there is still not much literature on IHDI and its application in Indonesia, especially in Jambi Province. This study aims to analyse the partial and simultaneous effects of fiscal independence (FI), private investment (PI), zakat performance (ZP) and economic growth (EG) on IHDI in Jambi Province. The data used is panel data in the form of time series data for 5 years, namely 2017-2022 and cross section data on 11 regencies / cities in Jambi Province. The data analysis used is descriptive analysis and panel data regression analysis with an econometric model approach using the Eviews 8 programme. The results showed that simultaneously FI, PI, ZP and EG had a significant effect on IHDI. Partially, there is a significant effect of FI, ZP and EG on IHDI.  The integration of key factors, studies in the Islamic context, measurement of the impact on IHDI, the use of econometric models and contributions to public policy are novelty in this study